2007
DOI: 10.1111/j.1365-3180.2007.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of non‐chemical weed control on hard surfaces

Abstract: SummaryWeed control research to date has mainly focused on arable land, especially regarding herbicides, but also regarding non-chemical methods. Some of these experiences can be applied to hard surface areas. However, weeds on hard surface areas cause problems that are different from those on arable land. Additionally, crop tolerance does not need to be considered when choosing an appropriate weed control method on these areas. The aim of this review is to describe current knowledge of weeds and weed control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 37 publications
0
62
0
1
Order By: Relevance
“…Among these tactics, the use of steaming promises to be useful because it efficiently transfers heat (Rask and Kristoffersen 2007) and reduces fire risk, especially in areas where dry plant residue is present (Hansson and Ascard 2002). However, there is limited information about the factors that determine the effectiveness of steaming as a POST weed control tactic.…”
mentioning
confidence: 99%
“…Among these tactics, the use of steaming promises to be useful because it efficiently transfers heat (Rask and Kristoffersen 2007) and reduces fire risk, especially in areas where dry plant residue is present (Hansson and Ascard 2002). However, there is limited information about the factors that determine the effectiveness of steaming as a POST weed control tactic.…”
mentioning
confidence: 99%
“…, 2001; Reichel, 2003; Kristoffersen et al. , 2004; Rask & Kristoffersen, 2007). Non‐chemical treatments mainly affect the above‐ground plant parts, whereas systemic herbicides, such as glyphosate, kill the entire plant and therefore only require one or two treatments per year (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated use of any weed control method is likely to cause a shift in the weed flora to resistant or more tolerant species. Thermal methods often favour the growth of grasses and dicotyledonous species with growth meristems close to the ground (Parish, 1989; Ascard, 1995, 1998; Hansson, 2002; Rask & Kristoffersen, 2007). In this study, the weed flora was dominated by well‐established grasses and this may reduce the effectiveness of the thermal treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature study on non-chemical weed control on hard surfaces (Rask & Kristoffersen, 2007) revealed a need of proper definition of efficiency of the weed control methods. Different methods to measure the effect of non-chemical treatments may lead to different results (Hansson, 2002).…”
Section: Introductionmentioning
confidence: 99%